PISA 2006 과학성취도에 대한 학생 및 학교 수준 맥락요인의 영향력 분석 - 염시창, 강대중 (교과교육학연구, 2011)
본 연구는 과학성취도에 영향을 미치는 학생 및 학교 수준 변수 중 맥락요인의 영향력을 분석하기 위해 수행되었다. 특히, 본 연구에서는 학생 수준의 변수와 학교 수준의 선행요인인 학교 배경변수를 통제한 상태에서 맥락요인인 과학 수업환경 변수의 과학성취도에 대한 영향력을 분석하였다. 본 연구는 OECD에서 주관하여 시행하였던 만 15세 대상의 PISA 2006 자료 가운데 우리나라 고등학교 139개 학교와 이들 학교에 내재되어 있는 4,158명의 학생의 자료를 분석대상으로 삼았다. 또한 2수준 다층모형을 통해서 분석을 시도하였으며, 더미변수 이외의 변수는 모두 전체 학교 평균치에 대한 편차점수로 변환하여 분석하였다. 분석 결과는 다음과 같다. 첫째, 학생 수준의 선행요인 중에서는 남학생, 그리고 부 학력수준이높은 학생의 과학성취도가 높았고, 맥락요인 변수 중 자기주도적 과학 공부시간, 과학흥미 및 과학가치가 결과변수인 과학성취도와 정적인 관련성을 보였다. 이에 반해 사교육 과학수업시간과 과학활동 정도는 과학성취도와 유의한 관계가 없었다. 둘째, 학교 수준의 선행요인 중에서 학교평균ESCS가 과학성취도에 정적 영향력을 미치는 것으로 나타난 반면, 과학교사 부족은 과학성취도에부적 영향력을 미치는 것으로 나타났다, 이는 향후 국가수준에서 자격을 갖춘 과학 교사를 증원하는데 정책적 지원이 필요하다는 점을 시사한다. 맥락요인의 변수 중에서는 학교평균 정규 과학수업시간이 과학성취도와 정적 연관성을 보인 반면, 과학클럽활동, 과학전시회활동, 과학경진대회 및과학주제활동과 같은 맥락변수는 유의하지 못한 것으로 나타났다. 마지막으로 본 연구에서는 학생및 학교 수준의 선행요인과 맥락요인의 영향력을 종합하여 논의 및 결론을 제시하였다. This study attempted to identify the influence of the curricular context factors within studentand school-levels on the science achievement of Korean students. The subjects of the study were 4,158 students nested within 139 high schools in Korea, and the data were from PISA 2006 focusing on science and collected information on student attitudes toward science by the OECD. The study used two-level model analyses. The variables, with the exception of dummy variables, were centered around the grand mean of each variable. The results of the study can be summarized as follows. Males or students whose fathers had higher educational levels showed higher science achievement scores. Among the context factors,self-directed science study time, science interest, and science values were positively related to science achievement, whereas private tutoring time on science and science activities had no significant relationship with achievement. At the school level, school average ESCS had positive effects on science achievement, while the shortage of science teachers showed negative effects on achievement. These findings suggest that, in the future, the government should increase the number of qualified science teachers on a national level. Among the curricular context factors,the average time of school science classes showed a positive relationship with science achievement, whereas other context factors at the school level were not related to achievement. KCI Citation Count: 13